2022
DOI: 10.3389/fbioe.2022.868734
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From CTF1-Modified Bone Marrow Stem Cells Promote Endometrial Regeneration and Restore Fertility

Abstract: Background: Thin endometrial tissue is a leading cause of embryo transfer failure, potentially contributing to sustained infertility and associated adverse outcomes. The application of exosomes derived from autologous or allogeneic bone marrow-derived stem cells (BMSCs) has been used to promote uterine repair following injury, and there is also prior evidence that stem cell transplantation can bolster fertility. Genetic modifications represent a primary approach to enhancing exosomal therapy strategies. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Recently, Zhang et al reported that treatment with exosomes derived from human umbilical cord mesenchymal stem cells significantly increased the endometrial thickness, expression of molecular markers of endometrial receptivity, and pregnancy rates in a rat model of thin endometrium [53]. Similarly, exosomes derived from bone marrow stem cells (BMSCs) and genetically modified BMSCs promote the regeneration of endometrial tissues and improve endometrial receptivity in a rat model [54]. Based on these findings, miR-205-5p mimics were transfected into exosomes derived from non-receptive AN3-CA cells to confirm their functional importance in endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al reported that treatment with exosomes derived from human umbilical cord mesenchymal stem cells significantly increased the endometrial thickness, expression of molecular markers of endometrial receptivity, and pregnancy rates in a rat model of thin endometrium [53]. Similarly, exosomes derived from bone marrow stem cells (BMSCs) and genetically modified BMSCs promote the regeneration of endometrial tissues and improve endometrial receptivity in a rat model [54]. Based on these findings, miR-205-5p mimics were transfected into exosomes derived from non-receptive AN3-CA cells to confirm their functional importance in endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes of bone marrow stem cells, such as these cells themselves, contribute to the restoration of the endometrium after damage-in a study on experimental animals (rabbits), activation of the TGF-β1/Smad signaling pathway by exosomes contributed to the reversal of EMT [126]. It was noted that a possible modification of MMSCs-exosome donors with hyperexpression of cytokine cardiotrophin-1-can more effectively contribute to the restoration of the endo-and myometrium in a situation where neovascularization can increase endometrium receptivity [127].…”
Section: Effect Of Mmsc-derived Extracellular Vesicles On Endometrial...mentioning
confidence: 99%
“…Zhu et al used an adenovirus vector to overexpress Cardiotropin-1 (CTF1), a cytokine in the IL-6 family ( Martinez-Martinez et al, 2019 ), transfected it into BMSCs, and extracted exosomes (C-BMSCs-Exos) from BMSC overexpressing CTF1. Compared to control BMSCs (BMSC-Exos), C-BMSC-Exos significantly promoted the proliferation, migration, and tube formation of human umbilical vein endothelial cells (HUVECs) in vitro , promoted endometrial regeneration and restored fertility in a rat endometrial injury model ( Zhu et al, 2022 ). Li X. et al (2020) transfected BMSCs with a lentivirus encoded by CXCR4 and isolated exosomes.…”
Section: Exosome Combined With Hydrogel In the Treatment Of Iuamentioning
confidence: 99%